Konstruksi Storyline Sebagai Strategi Komunikasi Company Profile PT. Aliyah Perdana Wisata - H, Muhammad Rizal; Butsiarah, Butsiarah; Ikhsan, Ahmad Nur; Mursalim, Mursalim (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2022)
PT. Aliyah Perdana Wisata is a company engaged in organizing Hajj and Umrah. PT. Aliyah Perdana Wisata since its inception has focused on the field of organizing Hajj and Umrah, and has dispatched thousands of pilgrims each year and provided the best service to pilgrims while in the holy land. In order for Aliyah Wisata to be better known by the wider community, a promotional media in the form of video motion graphics is needed so that the delivery of interesting information and able to convey information well to potential customers. This study aims to design a company profile video for PT. Aliyah Perdana Wisata through motion graphic animation to be better known by the wider community, especially in Makassar City. This study uses the MDLC (Multimedia Development Life Cycle) method which consists of 5 phases, namely the concept phase (concept), the design phase (design), the material collecting phase (material collection), the assembly phase (manufacture), the testing phase (testing) and distribution phase. The final result of this research is an animated motion graphic video as a company promotion media regarding the implementation of hajj and umrah.